Theoretical and Developmental Issues in the Syntax of Subjects: Evidence from Near-Native Italian - Belletti, Adriana; Bennati, Elisa; Sorace, Antonella (Natural language and linguistic theory, 2007)
This article reports the results of experiments targeting the production and interpretation of postverbal subjects, and null and overt pronominal subjects, by near-native speakers of Italian whose native language is English. The results directly bear on both theoretical issues and developmental acquisition questions. It is argued that properties related to the null-subject parameter are sensitive to discourse factors that determine the use of both postverbal subjects and pronominal subjects. More specifically, it is claimed that the availability of null pronominal subjects and the availability of postverbal subjects do not necessarily correlate. The near-native grammars analyzed here illustrate a special instance of this lack of correlation. Furthermore, near-natives show non-native-like behavior in the use of postverbal subjects, and in the overuse of overt pronominal subjects in tensed clauses. The proposal is put forward that, although resetting of the null-subject parameter has taken place in the speakers' L2 Italian grammar, the relevant L1 computations are preserved and accessed in L2 use, without violating any formal conditions; this is the source of non-target behavior. The analysis proposed exploits cartographic insights on discourse-related computations, and suggests that the principles of economy may be instantiated differently in native and near-native grammars.